Fitlight. ([s.l.] : FitLight, 2020)
Bestaat uit de set met 8 lampen, twee tablets/schermen en een adaptor - The world's most advanced wireless light training system. FITLIGHT® uses patented wireless light sensors and proprietary training programs to challenge users with engaging, powerful tasks. FITLIGHT® is designed to train the body and the brain, improving reaction time, mental accuracy, sensory processing and other neurocognitive attributes. By training the connection with what your eyes see and what your brain processes and how your body reacts, FITLIGHT® is designed to improve all elements of human performance.
Sportmateriaal SBE - te ontlenen in het SIC - mailen: imane.khouna@howest.be
Keywords: Sportmateriaal SBE